Ameloblastom. Case report - Ramos Perfecto, Donald (2008)
One of the tumours in the oral cavity of epithelial origin, with major damage at the bone or soft tissue is an Ameloblastom; although this is a benign tumour, its aggressiveness could lead to produce extensive destruction of the jawbone. In this report, one case is exposed, a male patient with clinical and diagnosis - X-ray radiographicof Ameloblastom.